The Permanent Resident : Excavations and Explorations of George Washington's Life - Levy, Philip, 1963- (Book collections on Project MUSE., 2022)
"This archaeological biography of George Washington uncovers the physical remains of the major sites he lived at or visited--from his childhood home near Fredericksburg to Barbados and Mount Vernon--while also narrating their many, and shifting, afterlives in American popular memory"--